WhatsApp-Based Drug Reminder Information System - Fatah, Haerul; Fauziah, Ari Zainal; Sidik, Akmal; Khofifah, Shofia; Wahyuni, Tri; Ermawati, Erni; Indriyanti, Indriyanti; Ichsan, Nurul (Program Studi Sistem Informasi Fakultas Teknik dan Ilmu Komputer, 2025)
Timely and accurate medication use is a critical factor in the success of treatment, especially for patients with chronic illnesses such as diabetes, hypertension, and heart disease. However, patient non-adherence remains a major challenge. Based on observations at Panglayungan Community Health Center (Puskesmas), Tasikmalaya City, data recording and visit reminders are still handled manually. This often leads to service delays, data errors, and high rates of patient absenteeism. To address these issues, this study designed and developed a WhatsApp-based medication reminder information system capable of sending automated notifications to patients according to schedules set by healthcare staff. The application includes features such as patient data management, visit scheduling, and automated message delivery via the WhatsApp API. The system was developed using the waterfall software engineering model, starting from requirements analysis, system design, implementation, and testing. Test results demonstrated that the system successfully delivered medication reminders on time and effectively reached patients. Moreover, integrating WhatsApp as a reminder medium proved to be user-friendly and widely accepted, as it does not require users to install additional applications. This system not only improves patient adherence to prescribed therapies but also assists healthcare providers in data management and patient monitoring more efficiently. Furthermore, the system was designed with a lightweight, responsive web-based interface to ensure ease of use for health center staff. With a structured database, it helps reduce administrative workload and minimizes the risk of data loss.